Safety assessment of novel polymer-silicon composites - from LCA perspective - Zhu, Huijun; Irfan, Adeel; Sachse, Sophia; Njuguna, James (Publications Office of the European Union, 2012)
The fast growing trend in the development of novel materials with potential applications in many industrial sectors has caused concerns over the environment and human health effect of the emerging activities and associated products. It is imperative that these concerns are addressed in a holistic manner as early as possible. As part of the NEPHH project, this study applied the LCA concept aiming to identify hazardous nanoparticles (NP) that could be released during the development and application of novel products, focusing on polymeric-silicon composites in recognition of their attractions to a wide range of industries, including construct engineering, automotive and aerospace.